ANALISIS EFEKTIFITAS MEDIA PEMBELAJARAN BERBASIS GAME EDUKASI DALAM PEMBEJARAN IPA DI SEKOLAH DASAR : A SYSTEMATIC LITERATUR REVIEW - Widianto, Dwi Nur; Rohmani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Educational game-based learning media is an innovation in education that raises the bar for science instruction in elementary schools by fusing entertaining and educational elements. This study aims to assess how educational game-based learning resources affect primary school students' scientific learning results. The method used is a Systematic Literature Review (SLR), and the data comes from Google Scholar. The literature search process involved several steps: the first stage produced 361,000 documents using the keyword "Learning Media"; the second stage added the keyword "Educational Game" and produced 16,300 documents; the third stage added the keyword "Science" and produced 7,340 documents; and the fourth stage added the keyword "in elementary school" and produced 2,490 documents. Filtering according to inclusion criteria also yielded seven relevant papers for further examination. The results of the study demonstrate that the use of instructional game-based learning resources considerably and favorably enhances primary school students' scientific learning outcomes. In addition to improving science literacy, these media can increase learning motivation, active student participation, and learning interest. The development of 21st-century skills like problem-solving, creativity, critical thinking, and teamwork is also aided by the use of educational games. Therefore, educational game-based learning resources can be an innovative and effective strategy to improve the quality of science education in elementary schools.